Echinacea as a Functional Ingredient in Immunocosmetics: Health and Educational Perspectives – A review - Jurczuk, Aleksandra; Bałdyga, Paulina; Froń, Oliwia; Romaniuk, Sergiusz; Kaczmarek, Aleksandra; Kaczmarek, Wojciech; Krakowiak, Magdalena (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: The cosmetics industry increasingly turns to natural ingredients that improve skin appearance and support its health. Echinacea, known for its immunomodulatory, antioxidant and anti-inflammatory properties, is gaining popularity as an active substance in immunocosmetics — products combining care with immune support. This article reviews the dermatological potential of selected species, mainly E. purpurea, E. angustifolia and E. pallida, assessing their role in strengthening skin immunity, regeneration and protection against environmental factors. Material and Method: A qualitative review was performed using PubMed, Scopus and Web of Science. Only peer-reviewed papers from the last decade focused on Echinacea’s dermatological effects were included; studies lacking empirical data were excluded. Results: Echinacea contains key bioactive compounds such as polyphenols (e.g., chicoric acid), alkamides and polysaccharides, which act synergistically on the skin. They reduce inflammation, neutralize free radicals and support epidermal renewal. The extracts influence immune cells like Langerhans cells and keratinocytes, enhancing innate immunity. Due to antimicrobial activity, particularly against Cutibacterium acnes, Echinacea is useful in acne care. Cosmetics with its extracts improve hydration, elasticity and may reduce wrinkles. Conclusions: Echinacea shows notable potential in immunocosmetics thanks to its multifunctional effects on skin health. Further research and careful formulation are essential for its safe and effective use in modern skincare.